La Gamificación como estrategia de comprensión lectora para los estudiantes del 2do de Bachillerato - Torres Hurtado, José Fernando (2023)
The current research arises due to the low results obtained in the reading comprehension of Ecuadorian students in the PISA-D report (2018) and in the tests taken by the National Institute for Educational Assessment (INEVAL) in 2019-2020 school year. The research analyzes the results in gamification in the reading comprehension of high school students, taking into account the literal and inferential levels. The current research is based on the criteria and operations for the literal and inferential level, proposed by Gordillo and Flórez (2009), Cervantes et al. (2017) and Ibarra (2020) and the evaluation scales (very superior, superior, medium, low and does not perform) proposed by the Ministry of Education (2020) in the instructions for student assessment. The methodological approach is qualitative in nature with an applied and descriptive scope. The research was designed in three moments: a) diagnostic evaluation, b) didactic sequence based on the gamification strategy (Kahoot, Educaplay and Quizizz) and c) closing evaluation. The results of the diagnostic evaluation showed that the students mostly perform on the low and medium scales in the literal and inferential reading levels. In the closing evaluation and after the didactic sequence, the results show that there is a better understanding of the texts used, and it is demonstrated in the analysis of the scales obtained, very superior and superior. To sum up, after the methodological process applied as a methodology, strategy and as a resource, gamification can be a good alternative that accompanies the teaching of reading at the literal and inferential level. Keywords: gamification, educational platforms, reading comprehension levels, didactic sequence, reading assessment.